Government System of the Islamic Kingdoms of the Archipelago (Case Study: Sultan’s Appointment, Authority, and Exemplar of Former Pekal Kingdom, Mukomuko) - Etry Mike (NEGREI: Academic Journal of Law and Governance, 2022)
Bengkulu Province used to have a number of small kingdoms as stated in historical records before 1685, namely the Empat Petulai Kingdom also known as the Depati Tiang Empat Kingdom with its Rajo Depati dwelled in the Bukit Barisan Mountain in Rejang Lebong Regency, on the coastal area of Bengkulu, the Sungai Serut Kingdom, the Selebar Kingdom in the Lembak area of North Bengkulu, the Sungai Lemau Kingdom in the Pondok Kelapa area of North Bengkulu, and the Anak Sungai Kingdom in Muko-Muko. This is field legal research. This research employs legal and historical research with the statute, historical, and comparative approaches. The specification of this research is descriptive-analytical. These small kingdoms did not form a state with absolute power. The kingdom consisted of hamlets led by a chief elected by the residents and the hamlet heads voluntarily joined the kingdom, where the King was the symbol of unity. The kingdom of the Anak Sungai Muko-Muko in its recent development declared itself the Sultanate of Pekal on July 29, 2017. The Supreme Chief of Kaum consists of seven clans in the community who inhabit the Pekal area, administratively occupying the Ipuh and Ketahun sub-districts in the district of Muko-Muko, Bengkulu Province. It is interesting to research this kingdom because it is the only former kingdom in Bengkulu included in the Yayasan Kerajaan Kesultanan Nusantara (YKKN).